Karakteristik dan Proses Pembelajaran Siswa Slow Learner - Dyah Esti Mandagani; Zain Nur Khusnaini; Nur Indah Aryati; Sigit Prasetyo; Izzatin Kamala (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
The lack of optimal teachers in facilitating the learning process of slow learner students will certainly have an impact on the learning outcomes obtained by them. The purpose of this study provides an overview of the characteristics of slow learner students in grade III SD N Wirosaban and the learning process in grade III SD N Wirosaban. This research uses qualitative research methods with a case study approach. The data collection techniques used are by observation, interviews and documentation. This research was conducted at SD N Wirosaban, which focused on examining the characteristics of slow learner students in grade III and the learning process. The instruments used are gadgets and stationery. The result of this study is the difference in the characteristics of students in general with slow learner students who are most dominantly seen in their cognitive. Slow learner students experience difficulties during the online learning process, while in offline learning students are more able to maximize during learning